Acidente vascular encefálico em vítimas de acidentes ofídicos: uma revisão sistemática com metanálise de dados individuais - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Snakebites are important neglected health problems due to their severity and frequency. Envenomation can cause local and systemic complications that depend on several factors such as: the snake involved, the amount of venom inoculated, the presence of comorbidities and the time until medical attention. Systemic complications can be fatal or cause outcomes with significant permanent sequelae, such as in cases of cerebral vascular impairment, caused by the interaction of venom toxins, in cases of stroke. This systematic review aims to gather and investigate the main clinical and epidemiological characteristics of victims affected by stroke resulting from snakebites and identify the factors associated with the main outcomes such as severity and risk of death. For this, searches were carried out in the main available databases: MEDLINE/PubMed, LILACS and Scielo. The criteria for developing this study took into account the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines, which consists of a checklist and flow diagram that guide the search and reporting of evidence from systematic reviews with the objective of maintaining the quality of the evaluation. 79 articles were included, including reports and case series, which had the main clinical and epidemiological information on the victims, totaling 101 reports. Regarding the type of stroke related to the interactions of venom toxins, ischemic stroke was the most reported, caused mainly by snakes from the Viperidae family. Factors such as the delay in receiving medical care and low Glasgow Scale scores, assessed during the victims' hospitalization, were identified as risk factors for the development of hemorrhagic stroke. Victims of hemorrhagic stroke have a higher risk of death, as do those who have a low score on the Glasgow scale. A significant portion of victims remain with long-term stroke sequelae and do not have follow-up or specialized treatments, reflecting the socioeconomic impacts generated by the global burden of the disease.
Keywords: Acidente vascular cerebral; Isquemia encefálica; Cobras venenosas; Mordeduras de serpentes; CIENCIAS DA SAUDE; Acidente vascular cerebral; Isquemia cerebral; Hemorragia cerebral; Acidente ofidico